Pengawasan Keuangan Daerah Dari Pengetahuan Dewan Tentang Anggaran Diperkuat Oleh Partisipasi Masyarakat - Mardianti, Rani; Defitri, Siska Yulia; Sukraini, Juita (CV. ITTC INDONESIA, 2024)
This research examines the influence of council budget information (X) on regional financial control (Y) and the influence of council budget information (X) on regional financial control (Y) by testing community participation (Z). The survey results show that congressional budget information (X) has no effect on regional budget control (Y). The results of testing this first hypothesis are given the value |tcount|. Tested 0.595 danlt; 1 > 0.05. Knowledge of the DPRD budget (X) then influences regional fiscal control (Y) which is controlled by regional community participation (Z). The results of testing this second hypothesis are presented by testing the interaction between the R^2 value in the regression equation (1) and the R^2 value in the regression equation (2). As a result, the R^2 value of regression equation (1) is lower than the R^2 value of regression equation (2) (0.008 and less than 0.241).